Lymphedema and edema of the lower limbs: what do foot and ankle orthopedists need to know? A narrative review - Ruela, Victor Hugo Morais; Bochi, Gabriela Silva; Souza Júnior, Eli Ávila (Journal of the Foot & Ankle, 2025)
Objective: To review in the literature updates on lymphedema and differential diagnoses of lower limb edema for foot and ankle orthopedists. Methods: This is a narrative review, and the search was conducted on the PubMed and SciELO databases, using established keywords. Articles published in the last 15 years were included. The research question was “What do foot and ankle orthopedists need to know about lymphedema and lower limb edema?” Results: Lymphedema is one of the causes of chronic lower limb edema, characterized by excessive lymphatic fluid in the interstitial medium due to impaired lymphatic drainage. It can be classified as primary or secondary lymphedema, with trauma being one of the most important etiologies of the latter. The diagnosis of this condition is primarily clinical, typically established through a thorough medical history and physical examination. Complementary examinations can evaluate indirect signs of lymphedema or direct signs of lymphatic dysfunction through lymphoscintigraphy. The differential diagnosis of chronic lower limb edema is challenging, and venous, cardiac, and traumatic etiologies, as well as lipedema, should be considered. Conclusion: A thorough clinical examination, combined with appropriately indicated diagnostic tests such as lymphoscintigraphy, is essential for the differential diagnosis of chronic lower limb edema—a common finding in orthopedic clinical practice. Level of Evidence V; Narrative review